Symptomatic assessment in patients undergoing full-house functional endoscopic sinus surgery for pansinusitis using nonpowered instruments through the Sinonasal Outcome Test-22 Questionnaire in the rural population - Saai Ram Thejas; Nampally Prashanth; Tekuru Yogesh; S B Nilavan; Madhamshetty Ritesh Raj; Samudrala Vipanchi (MRIMS Journal of Health Sciences, 2023)
Background: Functional endoscopic sinus surgery (FESS) is a powerful method to achieve good clearance of sinus disease and is being practiced for the better part of the last three decades. The Sinonasal Outcome Test (SNOT)-22 Questionnaire was developed as a modification of the SNOT – 20 in 2009 and helps in better understanding of the disease process before and after surgery as it includes the functioning of special senses. Objective: The objective of this study was to assess the role and reliability of SNOT-22 in pansinusitis undergoing full-house FESS. Materials and Methods: The study was conducted in a tertiary hospital in rural South India from July 2021 to December 2021. Two hundred and thirteen patients were evaluated, and out of these, only 69 patients met the inclusion criteria. Surgery was performed under general anesthesia using cold steel instruments. SNOT-22 was administered 1 day before surgery and after 12 weeks postsurgery. Observations and Results: The average preoperative score in the SNOT-22 scale was 46.16 out of a maximum of 110 and the average postoperative score was 18.70 (an improvement of 59.50%, P < 0.05). Forty-two males and 27 females made it to the final study. The most common age of the patient at the time of presentation was between 21 and 30. Conclusion: Performing a full-house FESS for pansinusitis in cases with improper follow-up can be done without any side effects provided they are monitored with the SNOT-22 Questionnaire. This study can help practitioners achieve good success rates with lower revision surgery requirements.